PREVALENCE AND HEMATOLOGY PROFILES OF ANEMIA IN PATIENTS WITH ACUTE LOWER RESPIRATORY INFECTION - Adi Wirawan, I Ketut; Ariawati, Ketut; Subanada, Ida Bagus (Medicina; Vol 43 No 2 (2012): Mei 2012)
Anemia remains a major health problem worldwide, both in developed or developing countries. Approximately, 30% of world population suffered from anemia, and half of it is due to iron deficiency anemia (IDA). Clinical aspect of iron deficiency is lack of immunity. Objectives of this study were to measure prevalence and anemia profile on hospitalized children with acute lower respiratory tract infection (ALRI). This study was a crossectional descriptive study, using children with diagnosed of ALRI in Sanglah Hospital Denpasar, on January-December 2009. Children aged 6-59 months with diagnosed of ALRI and admitted for this study was 74 children. Most of them were male (69%), aged 6-11 months (57%), and 61% suffered from pneumonia. Most children with ALRI (64%) suffered from anemia, and 80% of them suffered from IDA. At ALRI group who were diagnosed with IDA, the average concentrations of hemoglobin, MCHC, SI, TIBC and transferin saturation were 9.72 g/dl, 32.76 g/dl, SI 21.03 µg/dl, 364.19 µg/dl and 6.05% respectively. It was concluded that prevalence of anemia in patients with ALRI was 64%, and 80% of them were IDA. Most ALRI patients with anemia (76%) have less iron status.
Keywords: acute lower respiratory infection, children under five, anemia